2020
DOI: 10.1177/1042258720967314
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Perspective in Entrepreneurship Research

Abstract: The past decade has experienced a significant increase in the number of papers on the biology of entrepreneurship. This trend is aligned with the general interest in the biology of management studies as evidenced by the more than 300 articles already published (Nofal et al., 2018). It illustrates the progression of science along two dimensions. First is the drive to seek smaller units of analyses to identify the core mechanisms of action. Second is the opposing drive to seek larger units of analyses to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
1
21
0
2
Order By: Relevance
“…Our study contributes to expanding the nascent line of research on biological and psychophysiological perspectives in entrepreneurship (e.g., Nicolaou et al, 2021). Psychophysiological measurement is relatively new to entrepreneurship research.…”
Section: Research and Eye Trackingmentioning
confidence: 90%
“…Our study contributes to expanding the nascent line of research on biological and psychophysiological perspectives in entrepreneurship (e.g., Nicolaou et al, 2021). Psychophysiological measurement is relatively new to entrepreneurship research.…”
Section: Research and Eye Trackingmentioning
confidence: 90%
“…Recent research on mental health and entrepreneurship (Nicolaou et al, 2020;Torrès & Thurik, 2019) have revealed important relationships that cannot be ignored when considering the consequences of the pandemic infection control measures. The documented increase in Covid-19 related depression, if persistent, has important consequences for SMEs that need to rehire as the economy recovers.…”
Section: Individual Absorptive Capacitymentioning
confidence: 99%
“…Además, se reafirman estos miedos en aquellos jóvenes con familias de bajos ingresos económicos. Considerando los resultados encontrados, se sabe que el impacto de la educación empresarial es sensible al género y a la edad; también hay un impacto positivo para los varones, pero no pasa lo mismo con las mujeres, ya que, para ellas, se tiene un resultado negativo en sus intenciones emprendedoras (Brüne y Lutz, 2020;Hung, 2020;Koyuncuoglu, 2021;Nicolaou, Phan y Stephan, 2021). Los resultados encontrados contribuyen a los hallados por Wyrwich, Stuetzer y Sternberg (2016), quienes afirmaron que las mujeres tienen mayor probabilidad de sentir miedo al fracaso.…”
Section: Discussionunclassified
“…La literatura ha resaltado el estudio de la perspectiva biológica en el espíritu empresarial desde la genética, la neurociencia, el neurodesarrollo y el comportamiento empresarial: se afirma que la biología no hace que las personas se conviertan en empresarios, lo que sí contribuye es la influencia que los individuos reciben en diferentes etapas de sus vidas con relación a variables que giran en torno al emprendimiento. Se tienen hallazgos importantes que indican que la testosterona está asociada con participar en actividades de emprendimiento; además, en materia de la neurociencia se ha encontrado que los vínculos afectivos de los emprendedores con sus nuevas empresas son similares a los vínculos que se tienen entre padres e hijos (Nicolaou, Phan y Stephan, 2021). Por último, el espíritu empresarial es considerado un mecanismo importante que coadyuva al desarrollo económico por medio de la generación de empleos, la innovación y el bienestar (Boubker, Arroud y Ouajdouni, 2021;Seelig, 2015).…”
Section: El Emprendimiento Y La Educaciónunclassified